If are in Arithmetic progression , then if the value of is given by ,then enter your answer as .
Note: represents
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Arithmetic progression has a fixed constant as common differences. Finding the differences by transforming the equation gives l o g 3 ( 3 3 1 − x + 2 ) = l o g 3 ( 3 1 − x + 2 4 ( 3 x ) − 1 ) or more simply 3 1 − x + 5 = 1 2 ( 3 x ) , which equals to 3 + 5 ( 3 x ) = 1 2 ( 9 x ) . Here we can factorize as ( 4 ( 3 x ) − 3 ) ( 3 x + 1 + 1 ) = 0 Given that 3 x + 1 + 1 = 0 , then only 4 ( 3 x ) − 3 = 0 or x = l o g 3 ( 4 3 ) is the answer, hence a + b + c = 3 + 3 + 4 = 1 0